2012
DOI: 10.1007/s10585-012-9452-x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis

Abstract: Morbidity and mortality of breast cancer patients are drastically increased when primary tumor cells are able to spread to distant sites and proliferate to become secondary lesions. Effective treatment of metastatic disease has been limited; therefore, an increased molecular understanding to identify biomarkers and therapeutic targets is needed. Breast cancer metastasis suppressor 1 (BRMS1) suppresses development of pulmonary metastases when expressed in a variety of cancer types, including metastatic mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…More comprehensive analyses of complexes will be required in order to fully interpret these data. Corroborating these notions, we recently reported that BRMS1 expression alone was not sufficient to suppress metastasis using mouse models of metastatic mammary carcinoma [43].…”
Section: Discussionmentioning
confidence: 97%
“…More comprehensive analyses of complexes will be required in order to fully interpret these data. Corroborating these notions, we recently reported that BRMS1 expression alone was not sufficient to suppress metastasis using mouse models of metastatic mammary carcinoma [43].…”
Section: Discussionmentioning
confidence: 97%
“…Immunohistochemical analyses of osteocalcin was performed as previously described (Cook et al, 2013). Briefly, excised femurs were submerged in 10% neutral buffered formalin (Sigma, St Louis, MO) for fixation before decalcification with 10% EDTA and paraffin embedment.…”
Section: Methodsmentioning
confidence: 99%
“…At weaning (~3 weeks of age) mice were genotyped for presence of the PyMT transgene as previously described (12, 18). mtDNA haplotypes were also confirmed in all female transgene-positive F 1 progeny by RFLP (restriction fragment length polymorphism) analysis of PCR products screening for diagnostic mtDNA SNPs that differentiate between the FVB, C57BL/6, and BALB/c mtDNA, as previously described (17).…”
Section: Methodsmentioning
confidence: 99%